A Panel Data Analysis of the Relationship Between Air Pollutant Emissions, Economics, and Industrial Structure of China. Issue 6 (2nd June 2016) - Guo, Xiaopeng; Guo, Xiaodan
ABSTRACT: The purpose of this article is to investigate the relationship between China's industrial structure, economic position, and air quality. The PM2.5 emission is used as the air pollution indicator, the gross regional product (GRP) and the proportion of secondary industry as the local economic indicators, and the power generation and the freight volume as the developmental indicators of important industries. Using the panel data model, this article provided evidence that the GRP has positive effect on the PM2.5 emission and the power generation has a significant impact as well in several cities. But freight volume could not increase the PM2.5 emission significantly in most regions of China.